2020
DOI: 10.1155/2020/9675235
|View full text |Cite
|
Sign up to set email alerts
|

The Many Difficulties and Subtleties in the Cognitive Assessment of Chronic Hepatitis C Infection

Abstract: Since the discovery of HCV in 1989, several diseases have been related to chronic infection by this virus. Often, patients with hepatitis C virus (HCV) complain of cognitive impairment even before the development of hepatic cirrhosis, which they described as "brain fog." Several studies have proposed a link between chronic HCV infection and the development of cognitive alterations, but the inclusion of confounding factors in their samples significantly limits the analysis of the results. In this article, we wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…(2) the number of study participants was small, thus limiting the study's statistical power. However, this study's sample size is close to that found in the vast majority of studies available in the literature [6]; and (3) the examiners were not blinded to the participants' serological status, wich may influence the outcome of neuropsychological testing.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…(2) the number of study participants was small, thus limiting the study's statistical power. However, this study's sample size is close to that found in the vast majority of studies available in the literature [6]; and (3) the examiners were not blinded to the participants' serological status, wich may influence the outcome of neuropsychological testing.…”
Section: Discussionmentioning
confidence: 77%
“…However, several studies have included patients with liver cirrhosis, advanced stage of hepatic fibrosis, and depression; besides, some published papers did not report such associations. Therefore, the controversy about whether HCV infection could be a cause of cognitive alterations remains unknown [6,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations